Pendalaman Konsep Geometri dan Pembuatan Media Pembelajaran Bagi Guru-Guru SD Kota Soe - Wilfridus Beda Nuba Dosinaeng; Kristoforus Djawa Djong; Samuel Igo Leton; Meryani Lakapu; Yohanes Ovaritus Jagom; Irmina Veronika Uskono (Universitas Lancang Kuning, 2020)
This Activities is based on the previous analyzes about the performance of teachers in understanding geometry concepts. These results reveal facts about the difficulty of teachers in understanding and teaching geometry conceptually. Based on these findings, the aims of these activities were of deepening understanding of concepts and training teachers to teach geometry conceptually. This activity is focused on five sub-activities, namely: a) refreshment of geometrical concepts; b) repaired teacher’s misconceptions about geometry; c) reinforcement of teachers' understanding of the concept of geometry; d) enrichment; and e) the making and practice of using instructional media to overcome the difficulties of teachers in teaching conceptual geometry to their students conceptually. This activity went well, seen from the presence of the teachers to participate in activities that exceeded the initial target and based on the questionnaire distributed, 88.5% of participants stated that they were satisfied with this activity.